Live and Let Live: Experiences from a German City during World War I (KULT_online, 2012)
In his scholarly piece the American historian Roger Chickering examines the historical development of Freiburg during the years of World War I as an example case for a German metropolis. Like other historians, Chickering considers the First World War as a total war with all-encompassing influence on everyday life. This can be seen in his auspicious, varied study which is based on autobiographical and public sources and in which he describes in detail the experiences of Freiburg's population.